1997
DOI: 10.1021/la9701541
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Real-Time Ellipsometry of Putidaredoxin Adsorption on Gold Electrodes

Abstract: Adsorption of putidaredoxin (Pdx) on gold electrodes was studied using dynamic spectroscopic ellipsometry and differential capacitance. A method to account for the metal surface optical perturbation during protein adsorption at constant potential is described. The method is based on the concept of the charged transition layer which develops between metal substrate and adsorbate. Transition-layer charge was determined from the differential capacitance and the ellipsometry measurements in buffer solutions. A thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
2
27
0
Order By: Relevance
“…A Å 01.84 e T G T hca (m* e 0 m* g )bDVa abs , [8] The ER response of the tryptamine layer was analyzed as a shift in the p-p* transition of the solvated indole-like where a abs is the amplitude of the measured molar absorptivring. The shift was ascribed to the interaction of the electrode ity line in m 2 /mol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Å 01.84 e T G T hca (m* e 0 m* g )bDVa abs , [8] The ER response of the tryptamine layer was analyzed as a shift in the p-p* transition of the solvated indole-like where a abs is the amplitude of the measured molar absorptivring. The shift was ascribed to the interaction of the electrode ity line in m 2 /mol.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, Eq. [8] should contain a sum over derivposition has been investigated in differential absorption mea-atives of at least two Gaussian functions, each one with its surements (15). There is a clear dependence on pH, ion own set of parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain instances, a reversible electrochemical response from cyt c on bare gold or glassy carbon has been found just by careful choice of electrolyte solution (28). Rational electrode surface design for protein electrochemistry is increasingly being based on physical studies of the electrochemical interfaces (29)(30)(31)(32). Strategies with larger enzymes include use of electroactive groups in solution, or groups that are covalently attached to the electrode (22) or to the protein (19) surface.…”
Section: Electrochemical Protein Regenerationmentioning
confidence: 99%
“…Although both scanning tunnelling microscopy and atomic force microscopy (AFM) are being used to obtain direct information on biological molecules adsorbed at solid–liquid interfaces, STM has been preferred over AFM in most of these studies to obtain higher resolution and to lessen probe‐induced distortion in the imaged molecular shape. A study on adsorbed pdx layer on a gold electrode surface by ellipsometry has been reported (Reipa et al ., 1997). Here, we present STM investigations on pdx adsorption at the gold (111)–buffer interface and show that a thiolated mutant, C73S‐D58C, in which cysteine‐73 and aspartic acid‐58 are replaced by serine and cysteine, respectively, is necessary for oriented immobilization of the molecules on the gold surface.…”
Section: Introductionmentioning
confidence: 99%